The Prognostic Role of Optimal Cytoreduction in Advanced, Bowel Infiltrating Ovarian Cancer. (1st June 2015) - Bachmann, Robert; Rothmund, Ralf; Krämer, Bernhard; Brucker, Sara Y.; Königsrainer, Alfred; Königsrainer, Ingmar; Beckert, Stefan; Staebler, Anette; NguyenHuu, Phuc; Grischke, Eva; Wallwiener, Diethelm; Bachmann, Cornelia
ABSTRACT Aim: In locally advanced ovarian cancer with bowel involvement appropriate surgical treatment is still controversial. Objective was to delineate factors to select those most likely to benefit from radical surgery in patients with locally advanced ovarian cancer. Methods: Therefore, we retrospectively evaluated 207 consecutive patients with primary stage IIB-IV ovarian cancer who underwent primary surgery between 2000 and 2007. Every patient received stage-related surgery and adjuvant platinum-based chemotherapy. Median follow-up was 53.5 months. Data collected included stage, histology, extent of cytoreduction and type of bowel resection. Univariate survival analyses were performed to investigate variables associated with outcome. Results: Optimal cytoreduction (OCR) (R ≤ 1 cm) was achieved in 76.8%. Most patients presented histologic grade 2/3 (96.6%), serous ovarian cancers (84.1%) and lymph node involvement (52.2%). Complete cytoreduction (R = 0 mm) has significant best prognostic impact in FIGO IIB–IV (p = .026). Regarding bowel involvement, bowel resection was performed in 82 patients (39.6%). In this subgroup of patients complete cytoreduction led to significant better overall survival than R > 0 mm–1 cm, even in FIGO IIIC–IV patients (p = .027); this fact is independent of bowel resection. Noticeably, for survival bowel resection achieving residual tumor mass below 1 cm was also one main prognostic factor and even recurrence rate was associated with residual tumor mass. Conclusion: Our findings suggest that the major prognostic factor in patients with advanced ovarian cancer needing colorectal resection is completeness of cytoreduction. Therefore, in advanced ovarian cancer patients, multivisceral surgery is indicated to achieve OCR (R ≤ 1 cm) with or without bowel resection with best prognostic impact.